Pleomorphic adenocarcinoma of the breast: a case report - Zhang, Yunkun; Fan, Pengchao; Gao, Min; Cong, Rui; Wang, Qimin; Zhao, Dan; Zhang, Jian; Zhang, Yini; Wang, Lifen (Frontiers in Oncology, 2025)
This article comprehensively reports a case of pleomorphic adenocarcinoma of the breast, a rare breast salivary gland-type tumor. A mass with a maximum diameter of 3.2 cm was detected through ultrasound within the upper outer quadrant in a 74-year-old woman undergoing left breast total mastectomy and sentinel lymph node exploration. Microscopically, the central part of the tumor was mostly arranged in the solid structures, some of which were cribriform and contained blue-stained secretions, while the periphery of the tumor had striated and glandular duct-like arranged structures. Some tumor cells had visible nucleoli and nuclear fission, with sparse cytoplasm. Immunohistochemistry revealed ER (-), PR (-), HER-2 (0), Bcl-2 (+), P63 (-), Calponin (-), S100 (+), E-cadherin (+), and Ki-67 (20%+). The next-generation sequencing (NGS) assay revealed a missense mutation within exon 7 in PIK3CA, which is related to the treatment of breast cancer. The patient received 1 course of oral Capecitabine treatment after surgery and was followed up for 2 years with no recurrence.